Effect of inhaled and oral n-acetylcysteine on airway defense mechanism - Pappová L.; Kazimierová I.; Kocmálová M. (Sciendo, 2017)
Aim: N-acetylcysteine is the prototype of mucolytic agents. The aim of this study was to evaluate the acute and chronic effect of inhaled and oral N-acetylcysteine on airway reactivity, cough reflex and ciliary beat frequency and parameters of mentioned defense mechanisms were assessed in physiological conditions.